Implications of Halal Certification at LP3H (Lembaga Pendamping Proses Produk Halal) State Islamic University Sunan Kalijaga on the Investment Opportunity Set (IOS) of Halal Tourism Products in Yogyakarta - Barokatut Toyibah (Business Finance Analyst Co., 2025)
The impact of Halal certification facilitated by the LP3H (Lembaga Pendamping Proses Produk Halal) at Sunan Kalijaga State Islamic University, on the investment industry for Halal tourism products examines how the LP3H Halal certification process impacts the investment attractiveness of Halal tourism products. By ensuring compliance with Sharia principles, LP3H certification can increase confidence and attract Muslim travelers, Muslim travelers who seek experiences that are in accordance with their beliefs gain confidence through certificates. This can attract investors and increase demand for Halal tourism goods. In addition, Halal certification can also expand market access, both domestic and international, thus providing significant growth opportunities for investors. This research highlights the potential of the LP3H Halal certification program to open up promising investment opportunities in the field of Halal tourism products. This research contributes valuable knowledge for investors, policy makers, and stakeholders involved in the development of the Halal tourism sector.